On some current aspects and new approaches to scientific understanding of the national characteristics of Russian statehood formation and evolution - N. A. Omelchenko; T. V. Rastimeshina; Yu. V. Sinchuk (Управление)
The object of the study is the process of Russian statehood formation and historical transformation.   The subject of the study is the analysis of existing in the Russian scientific and public thought (pre-revolutionary and modern) different approaches to the interpretation of national features of Russian statehood foundations origin and evolution.   The authors emphasize a number of fundamental problems of Russian statehood development, which today require creative comprehension by scientific community. The article substantiates the position on the enduring significance of domestic researchers’ and thinkers’ conclusions about the uniqueness of the process of Russian statehood foundations origin in the Old Russian state, which was fundamentally different from similar processes in Western states, the Tsardom of Muscovy political system specificity, which consisted in the cathedral structure of the state and received ideological justification in the “autocratic sobornost” doctrine. Special attention has been paid to the conclusions related to assessing significance of the long coexistence in the Russian state of two parallel beginnings such as the monarchical vertical of power and the rich veche tradition, which compensated for the relative weakness of the monarchy in technical and political sense. For the first time the issue of what place in Russian statehood transformation was occupied by the Time of Troubles of the early 17th century has been investigated in detail. Attention has been drawn to the conclusions of pre-revolutionary scientists and thinkers about the determining role of the Time of Troubles, which it played in the new attitudes’ formation to the state and state power in Russian society, including in the context of modern interpretations. The determining role of zemstvo bodies in the years of the Time of Troubles in the collapsing state preservation and revival has been pointed out. The conclusion has been made about the similarity of the Russian system of power with the Byzantine model, traditionally characterized by a combination of a rigid monarchical vertical and horizontal of developed self-government. The role of the state idea uniting society in preserving stability and sustainability of any state has been emphasized.